Teaching competency among Islamic educators in Malaysia - Che Noh, Mohd Aderi; Mat Ludin, Mohd Sofian; Suhid, Asmawati (IDOSI Publications, 2013)
Effective education requires a teacher who has the attitude and a high competency for teaching. This article aims to present a study relating to the attitudes and competencies of Islamic Education teachers who are important assets for the development of students’ individualities. This study is a pilot study carried out to obtain quantitative data. Questionnaires were distributed to a total of 525 Islamic Education teachers in Malaysia. Descriptive and multivariate analyses were used for data analyses which include the mean, correlation and multiple regressions. The results showed the importance of teachers attitude towards the teaching profession and the high teaching competency to nurture a generation of high-quality students. Strictly speaking, attitude and teaching competency of Islamic Education teachers are very helpful in determining students’ learning achievement.